Real estate finance and investments - Brueggeman, William B.; Fisher, Jeffrey D. (New York: McGraw Hill, 2024)
"This book prepares readers to understand the risks and rewards associated with financing and investing both residential and commercial real estate. Concepts and techniques included in the chapters and problem sets are used in many careers related to real estate. These include investing, development financing, appraising, consulting, managing real estate portfolios, leasing, managing property, analyzing site locations, corporate real estate, and managing real estate investment funds. This material is also relevant to individuals who want to better understand real estate when making their own personal investment and financing decisions"--
Includes bibliographical references and index.
Keywords: Mortgage loans -- United States; Real property -- United States -- Finance